Visual Studio Hacks - Avery, James (O'Reilly Media, Inc., 2005)
With start-up templates for projects ranging from Windows applications to web services, and extensive help and on-line documentation, Visual Studio .NET might be mistaken for a tool for unsophisticated users. It's true that most developers soon discover that the basic operation of Visual Studio is fairly self-explanatory; less obvious are some of the suite's more advanced built-in features.Visual Studio .Net includes a wealth of little-used capabilities, is very customizable, has a complete automation model, and much more. On top of its regular feature set, there are hosts of free add-ins, macros, and power toys that can further enhance the functionality of Visual Studio. This book is all about exploring these things, and in doing so, becoming a better and more efficient developer. Developers will learn how to: Get the most out of projects and solutions, including getting down and dirty with the undocumented format of project and solution files Use these editor features to the fullest, and add additional functionality to the editor through the use of third-party add-ins Learn smarter ways to navigate the application and your own source code Customize shortcut keys, toolbars, menus, the toolbox, and much more Use the debugger successfully not only on your source code, but with T-SQL and scripting languages as well Automatically generate code Learn how the server can be used to interface with databases, services, and performance counters, as well as WMI Use and create Visual Studio add-ins to extend its functionality Offering valuable tips, tools, and tricks, Visual Studio Hacks takes you far beyond the suite's usual capabilities. You can read this book from cover to cover or, because each hack stands its own, you can feel free to browse and jump to the different sections that interest you most. If there's a prerequisite you need to know about, a cross-reference will guide you to the right hack.If you want to experience the full spectrum of Visual Studio's functionality and flexibility, you'll find the perfect guide for exploration in Visual Studio Hacks . Once the final page is turned, you can confidently say that you've been exposed to everything that Visual Studio .NET is capable of doing.